PERTANGGUNGJAWABAN BANK DALAM MEMBERIKAN GANTI RUGI TERHADAP NASABAH ATAS KELALAIAN BANK (STUDI PUTUSAN MAHKAMAH AGUNG NOMOR 2508K/PDT/2015) - KHAIRUN NISA (PREMISE LAW JURNAL, 2018)
DOSEN PEMBIMBING:1. Bismar2. Tan Kamello3. Sunarmi Banking world much depends on customers who save their money in banksand who makes loan to banks; thus, customers play one of the important factors inbanking business. In order to have customers, a bank needs to build trust that isaccountable to its customers. The objective of this study is to discover and analyzethe regulations of banking law in protecting the customers’ fund to find out howthe liability of a bank is, for a customer who becomes a victim for its negligence,and to find out the consideration of the panel of judges of the Supreme Court in acase in which customers’ money in the bank is gone due to the negligence of thebank.The research employs normative juridical research which analyzes theruling handed down by judges through court process which studies secondarydata consisting of primary, secondary and tertiary legal materials. The researchapplies the theory of legal protection and liability so that it can properly answerthe research question which is about the liability of a bank in payingcompensation for its negligence to a customer.Based on the results of the research, the liability of a bank in payingcompensation for its negligence is regulated in the laws and regulation thatprotect customers in Law on Customers’ Protection No.8/1999, Law No. 10/1998,and Law on Financial Service Authority No.21/2011. The liability of the bank inthe Ruling of the Supreme Court is to pay compensation to the customer as muchas the financial loss he/she suffers. It is suggested that the government renew LawNo. 10/1998 in order to protect bank customers directly because the law does notregulate strongly the protection for them. It is also recommended that electronictransaction system in banking meet the provisions stipulated in Law No. 11/2011so that bank negligence can be avoided. The liability of a bank to paycompensation should be stipulated and the amount of the compensation should bementioned in Law No. 10/1998. After the issuance of the Supreme Court’s Ruling,banks should implement the principles of prudence to prevent bad things andcustomers should also be careful in saving their money and should print theirsavings in the savings book every month to avoid things like the one in this case.Keywords: Liability, Bank, Compensation, Customer